P129 Quantification of longitudinal joint and cartilaginous changes within ankles with haemophilia joint degeneration using MRI imaging. (23rd April 2022) - Schaper, Madeleine; Sharrock, Megan; Wilkins, Richard A; Redmond, Anthony C
Abstract: Background/Aims: Haemophilia is an X-linked recessive genetic disorder characterised by episodes of spontaneous and traumatic intra-articular bleeding. 90% of bleeds are of musculoskeletal origin, with the ankle being most affected joint. Recurrent bleeding results in haemosiderin accumulation, linked to progressive, end-stage ankle haemarthropathy in adolescent and adult patients. Magnetic Resonance Imaging (MRI) is gold-standard for the evaluation of early soft tissue and cartilage changes in ankles with haemarthropathy. This study utilised MRI sequences to quantify longitudinal changes within the ankle joint, via changes in cartilage thickness (CT), subchondral thickness (ST) and joint space width (JS) over time. Methods: Clinical T1 Sagittal MRI scans of HJD ankles were selected (N = 5). Each patient had a minimum of two MRI scans available, at least one year apart, to allow for comparison of longitudinal changes. All images were identity coded but fully anonymised. The earliest available and most recent MRI scan were measured in three slices (medial, lateral and middle slice) and at different points along the joint space (anterior, middle and posterior). Measurements taken were cartilage thickness on the talar dome (CT) and the distance between the subchondral bone of the tibial plafond and talar dome (ST). The joint space width (JS) was then determined by subtracting CT from ST. Results: Chondral thickness measurements showed most reduction, particularly at the antero-lateral aspect (-0.4mm) compared to the antero-medial and middle sections, with -0.24mm and -0.34mm (Table 1 ). ST and JS reduction was predominantly seen in the anterior joint, with most reduction in antero-lateral joint (-1.13mm). The posterior joint showed minimal reduction in the postero-medial and middle sections, with the posterior-lateral joint space width increasing (0.2mm). Subchondral thickness and joint space measurements were variable and did not demonstrate linear change over time. Conclusion: A systematic longitudinal decrease in cartilage thickness was seen in the antero-lateral and antero-medial aspect of the ankle joint. The antero-lateral aspect of the ankle showed the greatest reduction in joint space and cartilage thickness. This suggests that this area of the joint is likely to provide the best early indications of haemarthropathy when using MRI as a diagnostic tool. Disclosure: M. Schaper: None. M. Sharrock: None. R.A. Wilkins: None. A.C. Redmond: None.